Building course semantic view for representing course content concisely. (2016) - Zhang, Shunxiang; Wang, Yin; Zhang, Shiyao; Zhu, Guangli
Concise semantic representation of a course can help students conveniently master the entire content of a course. Also, it can provide technology support for semantic searching of courses for some online systems such as e-learning system, and e-book market recommendation system. The main task of course semantic representation is how to concisely and completely represent the course content. This paper proposes a semantic representation method for Chinese courses. First, to concisely represent the course semantic, some course professional terms with hyponymy relation are zoomed (or merged) into a term. Second, association semantic existing in professional terms of a course is mined to represent course semantic (i.e., course knowledge). Finally, based on the condensed professional terms and the mined association semantic, course semantic view is built to make the course semantic more intuitive and visual. The experimental results show that the proposed model can represent courses semantics well.